Evaluation of the First Contact Physiotherapy (FCP) model of primary care: patient characteristics and outcomes. (December 2021) - Stynes, S.; Jordan, K.P.; Hill, J.C.; Wynne-Jones, G.; Cottrell, E.; Foster, N.E.; Goodwin, R.; Bishop, A.
Abstract: Objective: First Contact Physiotherapy (FCP) is a primary care model where expert musculoskeletal (MSK) physiotherapists undertake the first patient consultation, to enhance MSK-patient care and free-up GP capacity. The authors report the quantitative findings from the FCP National Evaluation (Phase 3) which evaluated the FCP model against success criteria. Design and setting: A mixed-methods 24-month service evaluation involving 40 FCP sites and 240 FCPs across England. Methods: An online platform collected patient-reported experience and outcomes following the FCP consultation and at 1, 2 and 3-months follow-up. These included the Keele STarT MSK Tool, pain intensity (0–10 NRS scale), Musculoskeletal Health Questionnaire (MSK-HQ, range 0–56), and Friends-and-Family Test. Results: Over 13 months, 2825 patients were invited by email and 24% ( n  = 680) completed their initial questionnaire. Their mean age was 56.2 (SD 14.9), 61% were female, ethnicity was 97% white, mean pain intensity was 6.1 (SD 2.13) and mean MSK-HQ score was 33.8 (SD 9.5). At 3-months follow-up ( n  = 370) there was a 2.8 (CI 2.5 to 3.1) mean pain intensity reduction from baseline, a mean 7.1 (6.0 to 8.2) score improvement in MSK-HQ and 64% reporting overall improvement (much better/better) since seeing the FCP. One of the six success criteria was not met; 29% of those in employment reported receiving specific work advice from the FCP (target ≥75%). Conclusion: Ahead of the planned scale-up of the FCP primary care model across the UK, this evaluation provides useful data on patients who access this service, their short-term clinical outcomes and whether key success criteria are being met.